INFLUENCE OF DIFFERENT METHODS OF SWITCH-GRASS CULTIVATION ON SOIL ORGANIC MATTER DYNAMICS AND BIOMASS PRODUCTIVITY - Taranenko, A. O.; Kulyk, M. I.; Taranenko, S. V.; Galytska, M. A. (Scientific Progress & Innovations, 2020)
Ecological aspects of energy crops growing are relevant at present. This is especially important for switch-grass cultivation on marginal lands and land-use change. The article presents the scientific ways of switch-grass (Panicum virgatum L.) cultivation with bean component – creeping lupine (Lupinus repens Kuptsov N and Miron.). The aim of our research was to study the content of organic matter in the soil and peculiarities of switch-grass biomass yield formation applying various-species sowing, taking into account N fertilization. The research tasks were to determine changes in the structure of switch-grass phytocenosis, the dynamics of soil organic matter content, level of dry switchgrass biomass yield depending on the method of growing and N fertilizing. The experiment was conducted in the conditions of the central Forest-Steppe of Ukraine on marginal soils. The experiment involved the cultivation of “Cave-in-Rock” variety of switchgrass in monoculture (Mo), and also combined (C) and mixed (Mi) crops with lupine and also applying N in the following amounts: 0 kg N ha-1, 15 kg ha-1, 30 kg ha-1, 45 kg ha-1, 60 kg ha-1. Research methods in agronomy, as well as special methods and recommendations for switch-grass cultivation were used in the experiment. Statistical data were calculated by STATISTICA V.6.0 and presented in graphs. According to the research results, the highest switch-grass yield was obtained in combined crops (14.4–15.0 t ha-1) using 15– 30 kg ha-1 of N; in mixed crops it reached the level of 14.7 t ha-1 using higher rate of N (45 kg ha-1). Positive effect of the bean component on the increase of soil organic matter content and obtaining additional N nutrition in combined and mixed crops was established. A significant increase in quantitative plant indexes (height and density of plant stand) and switch-grass biomass yield in combined and mixed crops was registered. This was confirmed by correlation analysis. Reliable relationship was established between switchgrass productivity and soil organic matter content (r=0.77 in mixed crops (Mi), and r=0.58 in combined crops (C)).